MULLA SADRA’S INTEGRATIVE EPISTEMOLOGY: REASON, INTUITION, AND REVELATION - Moh. Sholeh Baharis; Muh. Syahril Sidik Ibrahim (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2026)
This article examines Mulla Sadra’s integrative epistemology within the framework of Hikmah Muta‘āliyah, focusing on the relation between discursive reason, intuitive witnessing, and revelation. Using conceptual analysis and comparative philosophy, this study analyzes Sadra’s position in relation to the Peripatetic and Illuminationist traditions. The article argues that Sadra does not merely compromise between rational demonstration and intuition, but reconstructs epistemology through an existential model grounded in wujūd, substantial motion, and ʿilm ḥuḍūrī. The novelty of this article lies in reading Sadra’s epistemology as an integrative-existential structure that shifts knowledge from mental representation to presential and transformative knowing. The findings show that burhān provides rational coherence, shuhūd provides direct existential disclosure, and revelation provides the highest orientation of truth. This structure makes Sadra’s epistemology distinct from both Peripatetic representationalism and Illuminationist intuitionism. The article contributes to contemporary Islamic epistemology by showing that, in Sadra’s thought, knowledge is not only conceptual cognition but also existential participation and the transformation of the knowing subject.